Pharmacognostic standardization of a well known edible mushroom Volvariella volvacea - Krishnendu Acharya, Sandipta Ghosh, Ipshita Kundu (Journal of Applied Pharmaceutical Science, 2016)
From ancient times, Volvariella volvacea has been recognized as a dietary addition in many Asian and European countries. Clinical evaluations have also revealed that the fruit body contains a great diversity of pharmacologically active constituents that posses remarkable medicinal activities. However pharmacognostic studies of the mushroom have not been carried out so far. So the present study was conducted with a view to establish a pharmacognostic standard of the dried powder of V. volvacea. Study was executed on the basis of microscopic, physical characters and phytochemical parameters using standard methods. Fluorescence analysis of the dried powder was also conducted using different chemical reagents. On the other hand, a fresh methanol soluble extract was prepared and prelimiminary screening of phytochemicals revealed the presence of phenols, flavonoids, ascorbic acid, β-carotene and lycopene. In addition, HPLC profile was recorded and results showed existence of 12 peaks as detected at 278 nm which might be of phenolic compounds. Furthermore, DPPH radical scavenging activity (EC50-0.12 mg/ml) and total antioxidant capacity (23.75±1.25 μg ascorbic acid equivalent/mg of extract) were conducted to evaluate antioxidant potentiality of the methanol extract. All these above mentioned standards developed from this study will help in maintaining quality and purity as well as ascertain the identity and authenticity of dried powder of V. volvacea.
Keywords: Antioxidant property, HPLC, Medicinal edible mushroom, Microscopic characters, Pharmacognostic standardization.